Endocrine Therapy in the Current Management of Postmenopausal Estrogen Receptor‐Positive Metastatic Breast Cancer. (May 2017) - Kaklamani, Virginia G.; Gradishar, William J.
Abstract: Metastatic breast cancer (MBC) results in substantial morbidity and mortality for women afflicted with this disease. A majority of MBCs are hormone‐responsive and estrogen receptor‐positive, making endocrine therapy (ET) an integral component of systemic therapy. With a primary goal of minimizing the effects of estrogen on hormone‐responsive MBC, ETs are among the first targeted treatments that aim to inhibit the influence of estrogen receptor activation on tumor proliferation. Several biochemical mechanisms have been the focus of drug development for treatment, including selective estrogen‐receptor modulation, aromatase inhibition, and selective estrogen‐receptor degradation. Treatments that exploit these mechanisms have improved survival and quality of life for women with MBC. However, in many cases, resistance to ET limits their effectiveness. Elucidation of the complex cellular signal cascades involved in the development of acquired resistance to ET and the interrelationship of growth factor signaling and estrogen responsiveness have characterized components of these pathways as attractive targets for drug development. Based on these insights and with the aim of overcoming hormone resistance, targeted therapies are emerging as useful treatments for MBC. This article reviews current endocrine treatments of MBC as well as recent and ongoing study of combination treatments and targeted therapies that interfere with cellular proliferation pathways as means of overcoming resistance. The Oncologist 2017;22:507–517 Implications for Practice: This review provides medical oncologists and other oncology health care providers with a current understanding of the rationale for endocrine therapy in estrogen receptor‐positive metastatic breast cancer and the efficacy and safety profile of available treatment options. Additionally, current concepts regarding the development of treatment resistance and the treatment strategies for overcoming resistance are discussed. Enhancing the current information and the understanding of these topics will assist clinicians in evaluating optimal treatment options for their patients. Abstract : Endocrine therapy is an integral component of systemic therapy for metastatic breast cancer. In addition, targeted therapies are emerging as useful treatments. This article reviews current endocrine treatments of metastatic breast cancer, as well as studies of combination treatments and targeted therapies that interfere with cellular proliferation pathways, as a means of overcoming resistance.